(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
Much has been written about the plight of teachers and how they have been devalued within the context of US society (e.g., Goldstein, 2015). Issues related to poor pay, cuts to pension plans, diminished bargaining power, school disinvestment, an obsession with high stakes standardized testing, an emphasis on merit pay, and questionable evaluation tactics have all been problems teachers have faced for decades (Bruno, 2018; Giroux, 2012). In recent years, teachers in the United States —particularly those working in public schools—have also been scapegoats in what might be regarded as a reactionary populist backlash against critical pedagogy and equitable diversity. To use language recently employed by Stephen Steinberg (2022), this backlash is part of a “counter-revolution” that has been gaining momentum and seeks to roll back rights, values, ideals, and practices that have characterized the post-Civil Rights era in the United States. Although Steinberg is referring primarily to the reconfiguration and re-entrenchment of systemic racism in the US since the 1960s, the idea of a counter-revolution is also discernible in recent efforts to limit or outright ban American schools from teaching critical aspects of US history and society.